Violet stimulated luminescence signal from electronic components for radiation accident dosimetry - Bassinet, Céline; Kreutzer, Sebastian; Mercier, Norbert; Clairand, I. (Radiation measurements, 2017)
Due to recent technological advances, new optical stimulation sources with higher energies became commercially available. In the present work, laser diodes emitting in the violet (∼405 nm) were used to investigate dosimetric characteristics of the violet stimulated luminescence (VSL) signal from electronic components (resistors and inductors) extracted from mobile phones. All component types exhibit higher sensitivity using violet stimulation than using blue one. The sensitization was negligible after 10 cycles of irradiation and measurement. The dose response was linear from 0.6 Gy to 30 Gy. Additionally, signal fading of one type of inductors was studied. Results were similar for blue stimulated luminescence (BSL) and VSL signals. Fading measurements performed at 40 °C after a preheat (125 °C hold for 10 s) or at 125 °C indicated low fading rates (∼95% of signal remaining 1 h after irradiation). These preliminary results appear to be promising for retrospective dosimetry.
Online veröffentlicht: 3. Mai 2017, Artikelversion: 30. November 2017
Gesehen am 27.03.2025